The effect of creatine supplementation on two 700-m maximal running bouts - Terrillion, K. A.; Dolenger, F. A.; Kolkhorst, F. W.; Joslyn, S. J. (International Journal of Sport Nutrition and Exercise Metabolism, 1997)
The research literature is inconclusive regarding the benefit of creatine supplementation on running performance. This study compared creatine and placebo conditions on running performance in 12 male competitive runners. Two 700-m runs were performed on two occasions. Prior to the second occasion, one group of six ingested 6 gm of sucrose four times per day for five days, and the other ingested 5 gm of creatine monohydrate plus 1 gm of sucrose on the same schedule. It was found that creatine supplementation did not enhance performance nor affect peak blood lactate, body weight, or total body water. Implication. Creatine supplementation over five days did not affect running performance.